Single tier GPS tracking system using GSM technology / Jarimi Jasni - Jasni, Jarimi (2013)
One of the major factors contributing to the loss of laboratory equipment in the university is displacement of the equipment by the person in charge or taken out by illegal person. Recently, Global Positioning System (GPS) tracking device is one of the popular techniques in tracking the location of the target The objective of this project is to develop a single tier GPS tracking system using GSM technology. In addition, the design and scope of the project will be flexible enough to support different environment without involving the third party company. This project utilized GPS and GSM module with microcontroller board based on the ATmega328 (Arduino Uno). The module comes with a Quad band GSM module and supports GPS technology for satellite navigation. This project allows tracking of the missing or stolen equipment based on the received SMS that contains GPS data (Latitude and Longitude) that is sent by the GSM module to the end users.